New and little-known bees of the genus Sphecodes Latreille, 1804 (Hymenoptera: Apoidea: Halictidae) from the Himalayas - Astafurova, Yulia; Proshchalykin, Maxim (European Journal of Taxonomy, 2020)
An annotated list of twenty species of rarely collected and little known bees of the genus Sphecodes Latreille, 1804 (Hymenoptera: Apoidea: Halictidae) from the Himalayas is given. Sphecodes bluethgeni sp. nov. is described from Bhutan. Three species are newly recorded from the Himalayas: S. binghami Blüthgen, 1924, S. kershawi Perkins, 1921 and S. laticeps Meyer, 1920. Based on type specimens, new synonymies have been proposed for Sphecodes cameronii (Bingham, 1897) = S. armeniacus Warncke, 1992 syn. nov.; S. gibbus (Linnaeus, 1758) = S. indicus Bingham, 1898 syn. nov.; and S. invidus (Cameron, 1897) = S. nigrobasalis Meyer, 1922 syn. nov. A lectotype is designated for Sphecodes sikkimensis Blüthgen, 1927. Illustrated keys to males and females of all species known from the Himalayas and an updated checklist of the 26 Himalayan species of Sphecodes are provided. Additionally, one new species from neighboring Uttar Pradesh (India), Sphecodes uttaricus sp. nov., is here described as new and included due to its close relationship to the Himalayan S. sikkimensis Blüthgen, 1927.